Auditors’ Perception of Their Regulator Within Their Social Group - Johnson-Snyder, Anna J.; Killingsworth, Brenda L.; Reed, April H.; Eseryel, U. Yeliz (Journal of Leadership, Accountability and Ethics, 2022)
Although copious literature exists on the judgment and decision-making (JDM) process, there is primarily anecdotal research on the personal perception of a regulatory body, such as the US Public Company Accounting Oversight Board (PCAOB). However, none have investigated its statistical impact on experts’ evaluation of another expert’s decision. A survey was conducted on 74 experienced auditors’ in-group members’ judgments and their perception of the regulator (PCAOB) to better understand the social group’s impact on professional judgments. The results reveal auditors’ evaluative decisions are positively associated with their perceptions of the regulator, inspection reports usage, and views of the PCAOB’s effectiveness.